Art for art's sake?: The impact of arts education - Winner, Ellen; Goldstein, Thalia R.; Vincent-Lancrin, Stéphan (Centre for educational research and innovation, 2013)
Arts education is often said to be a means of developing critical and creative thinking. Arts education has also been argued to enhance performance in non-arts academic subjects such as mathematics, science, reading and writing, and to strengthen students academic motivation, self-confidence, and ability to communicate and co-operate effectively. Arts education thus seems to have a positive impact on the three subsets of skills that we define as "skills for innovation": subject-based skills, including in non-arts subjects; skills in thinking and creativity; and behavioural and social skills.This report examines the state of empirical knowledge about the impact of arts education on these kinds of outcomes. The kinds of arts education examined include arts classes in school (classes in music, visual arts, theatre, and dance), arts-integrated classes (where the arts are taught as a support for an academic subject), and arts study undertaken outside of school (e.g. private music lessons; out-of-school classes in theatre, visual arts, and dance). The report does not deal with education about the arts or cultural education, which may be included in all kinds of subjects.The impact of arts education on other non-arts skills and on innovation in the labour market should not be the primary justification for arts education in todays curricula. The arts have been in existence since the earliest humans, are parts of all cultures, and are a major domain of human experience, just like science, technology, mathematics, and humanities. The arts are important in their own rights for education. Students who gain mastery in an art form may discover their lifes work or their lifes passion. But for all children, the arts allow a different way of understanding than the sciences. Because they are an arena without right and wrong answers, they free students to explore and experiment. They are also a place to introspect and find personal meaning.